Effectiveness of Illustrated Poster–Sticker Media on Elementary School Students’ Vocabulary Memorization: Efektivitas Media Poster-Stiker Bergambar terhadap Hafalan Mufrodat Siswa SD - Siti Hasna Nabila; Suhartono Suhartono; Khuloud Alouzi (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
Arabic learning in elementary school plays an important role in building the foundation of language skills, particularly in mastering mufrodat (vocabulary). However, students often experience difficulties in memorizing and recalling vocabulary due to conventional teaching methods and the limited variety of learning media. This study aims to examine the effectiveness of illustrated poster–sticker media in improving students’ ability to memorize Arabic vocabulary. The research employed a quasi-experimental method with a one-group pretest–posttest design involving 15 fourth-grade students of Saudah class at SDIT Imam Syafii Cendikia Pekanbaru. Data were collected through pretest and posttest assessments and analyzed using the Wilcoxon test, yielding a significance value of 0.003. The findings indicate a significant improvement between the pretest mean score (52) and posttest mean score (98), demonstrating that poster–sticker media is effective in enhancing students’ vocabulary memorization. The integration of visual elements and simple activities aligns with multimodal learning principles that strengthen memory retention. The novelty of this study lies in the simultaneous integration of posters and stickers as an innovative approach to vocabulary instruction in elementary-level Arabic learning. Keywords: Dual Coding Theory, Mufrodat, Multimodal Learning Theory, Visual Media.